Enhanced efficiency and air-stability of NiOX-based perovskite solar cells via PCBM electron transport layer modification with Triton X-100. Issue 42 (18th October 2017) - Lee, Kisu; Ryu, Jaehoon; Yu, Haejun; Yun, Juyoung; Lee, Jungsup; Jang, Jyongsik
Abstract : In this work, a phenyl-C61-butyric acid methyl ester (PCBM) electron transport layer was modified with Triton X-100, and this improved the photovoltaic performance and air-stability of perovskite solar cells. Abstract : We modified phenyl-C61-butyric acid methyl ester (PCBM) for use as a stable, efficient electron transport layer (ETL) in inverted perovskite solar cells (PSCs). PCBM containing a surfactant Triton X-100 acts as the ETL and NiO X nanocrystals act as a hole transport layer (HTL). Atomic force microscopy and scanning electron microscopy images showed that surfactant-modified PCBM (s-PCBM) forms a high-quality, uniform, and dense ETL on the rough perovskite layer. This layer effectively blocks holes and reduces interfacial recombination. Steady-state photoluminescence and electrochemical impedance spectroscopy analyses confirmed that Triton X-100 improved the electron extraction performance of PCBM. When the s-PCBM ETL was used, the average power conversion efficiency increased from 10.76% to 15.68%. This improvement was primarily caused by the increases in the open-circuit voltage and fill factor. s-PCBM-based PSCs also showed good air-stability, retaining 83.8% of their initial performance after 800 h under ambient conditions.